Vagal responses during cardioneuroablation on different ganglionated plexi: Is there any role of ablation strategy?. (1st April 2020) - Aksu, Tolga; Guler, Tumer Erdem; Bozyel, Serdar; Yalin, Kivanc
Abstract: Background: Cardioneuroablation has been used to treat vagally mediated bradyarrhythmias (VMB). The aim of this study is to assess vagal response (VR) characteristics during radiofrequency catheter ablation (RFCA) with different ganglionated plexus (GP) order. Methods: A total of 49 consecutive patients with VMB who underwent cardioneuroablation were enrolled. GPs were identified by electroanatomic-mapping-guided strategy. After all GP targets have been identified, patients were divided into 2 groups according to GP ablation strategy. In the left side first group, ablation order of GPs were left superior GP (LSGP), left inferior GP (LIGP), right superior GP (RSGP), and right inferior GP (RIGP). In the right side first group, ablation order was RSGP, RIGP, LSGP, and LIGP. Results: In the left side first group, LSGP was the most common GP site at which a VR was observed (36 of 40 cases, 90%). LIGP causes a VR in 9 of 40 (22.5%) cases. In the right side first group, VR was seen only 2 of 9 (22.2%) cases. Comparison of ablation strategy demonstrated a significant difference in VR during ablation on LSGP between groups. Despite, LSGP was the most common GP site at which a VR was observed both groups (90% in left side first group vs 11.1% in right side first group, p < 0.0001). In remaining GPs, VRs were not dependent on the ablation strategy and were not statistically different between groups. Conclusion: The present study demonstrates that the characteristics of VR during RFCA might change according to ablation order of GPs. Highlights: Different ganglionated plexus sites demonstrate different vagal response characteristics during radiofrequency application. Characteristics of vagal response may change according to ablation order and selective innervations principles of ganglionated plexi. Cardioneuroablation can effectively prevent recurrent spontaneous syncopal episodes not only in patients with refractory vasovagal syncope, but also in patients with sinus node dysfunction and functional atrioventricular block regardless of ablation order.